HEMATOLOGICAL DISORDERS OF PROPYLTHIOURACIL IN THYROID PATIENTS AT TERTIARY CARE HOSPITAL OF HYDERABAD: Propylthiouracil in Thyroid - Shaikh, Uzma Naz; Ghoto, Muhammad Ali; Dayo, Abdullah; Arain, Mudassar Iqbal; Khan, Jibran (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find out the frequency of anemia, agranulocytosis and thrombocytopenia in hyperthyroid patients after the use of propylthiouracil.Study Design: Cross sectional study.Place and Duration of Study: Out Door Patients Department and Pathology Laboratory in Liaquat University Medical & Health Sciences, Hospital Hyderabad/Jamshoro, from May 2016 to Apr 2017.Methodology: Two hundred cases, comprising of adult patients were categorized into five groups, age group 15-30 years 79 (39.5%) patients presenting the highest out of total, age group 31-45 years 68 (34%) patients, age group 46-60 years 36 (18%), age group 61-75 years 14 (7%) patients, age group >75 years 3 (1.5) patients. Complete blood count was analyzed on Sysmex Kx21 and thyroid profiles were analyzed on Elecysis 2010 from the Pathology Department. SPSS version 22 was used for data analysis.Result: Out of total patients, 32 (16%) were males and 168 (84%) were females with mean age of 37.44 ± 14.82 years. Majority of patients 68 (34%) were anemic, while 4 (2%) had agranulocytosis and 11 (5.5%) had thrombocytopenia. Headache was reported in 111 (55.5%), exophthalmos in 106 (53%), sore throat in 172 (86%), fever in 136 (68%) and weight loss in 95 (47.5%) patients.Conclusion: Propylthiouracil causes defective hematopoiesis in hyperthyroid patients because propylthiouracil has adverse suppressive effects on bone marrow.